Study protocol for a randomised, phase II, double-blind, experimental medicine study of obinutuzumab versus rituximab in ANCA-associated vasculitis: ObiVas - Dominic Paul McGovern; Mark E McClure; Matthew Coates; Simon Bond; Marcos Martinez Del Pero; Kim Mynard; Jacinta Lee; Rona M Smith; David R Jayne; Menna Ruth Clatworthy; Rachel B Jones (BMJ Open, 2024)
Introduction Relapses in ANCA-associated vasculitis (AAV) increase the incidence of end-organ damage and their prevention requires prolonged immunosuppressive therapy. Rituximab, a type I anti-CD20 B cell depleting monoclonal antibody, is the current standard of care for induction of disease remission. Rituximab is not always effective and is associated with a high subsequent relapse risk. Obinutuzumab is a type II anti-CD20 humanised monoclonal antibody with the potential to obtain greater tissue B cell depletion than rituximab and reduce relapse risk in AAV. Methods and analysis ObiVas is a randomised, phase II, double-blind controlled trial that will compare the mechanistic effects of rituximab and obinutuzumab in the induction treatment of patients with AAV positive for proteinase 3 ANCA (PR3-ANCA). 26 patients, either newly diagnosed or relapsing, will be recruited from a single centre and randomised in a 1:1 ratio to receive 1000 mg rituximab or obinutuzumab as induction therapy on days 1 and 15, alongside a tapering glucocorticoid regimen. The primary end point is CD19 + B cell depletion in nasal-associated lymphoid tissue (NALT), assessed as change from baseline to week 26. Secondary outcomes will compare the safety and clinical efficacy of rituximab and obinutuzumab and their impact on immune biomarkers, including tissue and peripheral blood lymphocyte subsets and PR3-ANCA binding levels. Patients are followed through to week 78. The trial opened for recruitment in January 2023 and is forecasted to complete recruitment by the end of 2024. Ethics and dissemination For all patients, informed written consent will be obtained in keeping with Good Clinical Practice. Trial results will be disseminated to the relevant scientific, clinical and patient communities on trial closure. NALT data analysis will start before trial completion. Other analyses will be reported after trial completion. This trial was given ethical approval by Edgbaston (West Midlands) Research Ethics Committee (approval reference 22/WM/0174). Trial registration number ISRCTN13069630 .